Cone pathway function in relation to asymmetric carotid artery stenosis: correlation to blood pressure. (8th June 2012) - Kofoed, Peter Kristian; Munch, Inger Christine; Holfort, Stig K.; Sillesen, Henrik; Jensen, Leif Panduro; Iversen, Helle K.; Larsen, Michael
Abstract. Purpose: To examine retinal function in relation to retinal perfusion pressure in patients with carotid artery stenosis. Methods: Thirteen patients with carotid artery stenosis without clinical eye disease underwent assessment of ophthalmic artery systolic blood pressure (OSP) by ocular pneumoplethysmography, carotid artery obstructive disease by ultrasonography, intraocular pressure by applanation tonometry, retinal perfusion by fluorescein angiography and retinal function by multifocal electroretinography (mfERG). Data analysis compared the eye on the most stenotic side with the fellow eye in the same patient. Results: Ophthalmic systolic pressure was 95.8 ± 13.1 mmHg on the side with the highest degree of carotid artery stenosis (mean 94.0%) and 111.7 ± 10.3 mmHg in the fellow eyes on the side with the lesser degree of stenosis (mean 33.9%). Summed mfERG implicit times (N1 and P1) were 3.4% and 2.0% longer (p = 0.013 and 0.021), and N1 and P1 amplitudes were 18.0% and 16.0% (p = 0.0041 and 0.020) lower in eyes on the side with the higher stenosis compared with the contralateral eyes. Shorter implicit times and higher amplitudes were correlated with higher brachial systolic arterial blood pressure (p = 0.0028, 0.011, 0.041 for N1, P1, N2 implicit times, respectively, and p = 0.0086, 0.016, 0.040 for N1, P1, N2 for amplitudes, respectively, corrected for OSP). Conclusion: Cone function deviation was observed in clinically healthy eyes on the side with highest degree of carotid artery stenosis and was found correlated to arterial blood pressure.